Endothelium-dependent vasodilatory effect of Smilax china Linn. water extract via PI3K/Akt signaling. (26th May 2020) - Tettey, Clement Okraku; Yang, In-Jun; Shin, Heung-Mook
Abstract: Objective: The objective of this study was to investigate the pharmacological effect of Smilax china Linn. water extract (SCLWE) on vascular relaxation and its underlying biochemical mechanisms. Methodology: Isolated rat aortic rings were pre-constricted with phenylephrine (PE). This was followed by the cumulative addition of SCLWE. The effect of endothelial nitric oxide and PI3K/Akt on the SCLWE-induced vasodilation was investigated by the pretreatment of endothelium-intact aortic strips with or without N G -nitro-L-arginine methyl ester (L-NAME) or wortmanin before constriction with PE. Results: Treatment of PE (1 μM)-pre-contracted aortic strips with SCLWE induced endothelium-dependent relaxation, which was attenuated by L-NAME and wortmanin. Further studies using HUVECs indicated that nitrite production, eNOS and PI3K/PKB (Akt) phosphorylations were increased after exposure to SCLWE but was attenuated by pretreatment with wortmanin. Conclusion: These results suggest that SCLWE induces vasodilation by augmenting NO production in endothelial cells via PI3K/Akt-dependent eNOS phosphorylation.